Evaluation Of Fluorescent Staining For Improvement In Diagnosis Of Pulmonary Tuberculosis In Sputum Smear Negative Cases - R R JAIN,; N M KAORE,; V K RAMNANI, (International Journal of Pharma and Bio Sciences, 2012)
Bright field microscopy of sputum after ZN staining is the backbone of revised national tuberculosis control program (RNTCP) for diagnosis of pulmonary tuberculosis. But reduced sensitivity in overburdened RNTCP centers and HIV-TB co-infection necessitates the use of newer modalities to increase the diagnostic yield. A cross sectional prospective analytical study was done from June 2011 to August 2011, to look for increase in sensitivity in diagnosis of pulmonary tuberculosis by examination of sputum smear negative cases by fluorescent microscopy. Two sets of smears were prepared, of which one set of smear was subjected to ZN stain to confirm sputum smear negativity. The second set of slides was stained collectively by fluorescent stain and observed by Labomed binocular LED Microscope with fluorescent attachment. All the data was maintained in Microsoft Office Excel for analysis Four out of 160 (2.50%) enrolled were found out to be positive on reconfirmation and excluded. Out of 156 samples subjected to fluorescent staining, thirteen samples were reported positive by two independent observers. This rise of 8.33 % over routine RNTCP method which was able to diagnose 5.88% (10/170) cases is highly significant with P<0.017 (χ2=5.686). These 13 additional cases diagnosed constitute 92.85% increase in case detection when compared to RNTCP method which only detected 14 cases.Fluorescence microscopy is much more effective in diagnosis of paucibacillay cases with ease of identification and less eye-strain.